Larry Bond's Red dragon rising : blood of war - Bond, Larry (Bond, Larry. Red dragon rising., 2013)
While U.S. Army Major Zeus Murphy leads a covert Vietnamese counterattack against China , SEAL Lieutenant Ric Kerfer is sent by the president to destroy a Vietnamese doomsday weapon capable of destroying Southeast Asia.